Poglądy węgierskiej nauki prawa państwowego na rady narodowe: [Theoretical aspect of the position of People's councils in Hungarian constitutional law] (Studia Prawnicze / The Legal Studies, 1981)
The Author points out to similar ways of development of the constitutions of european socialist countries and to appropriateness of their common scientific studies. Cooperation of Hungarian constitutionalists with the Polish ones, and especially with prof. S. Zawadzki, is particularily valuable.Development of Hungarian constitutionalism has its peculiarities. Constitutional changes had been preceded by economic reforms and the reform of the system of councils (election law of 1970 nr. III and law on people's councils of 1974 nr. I).In Hungarian science, the character of the councils' power was widely discussed on the basis of the law on people's councils of 1974. It was pointed out that the councils are organs of state power and the representation of the people.From among the tasks of the councils, representation of the interests of a given territory was put forward into the first rank by the reform of 1971-1974. Also, the reform stresses the character of the councils as organs of self-government with the aim of ever wider fulfillment of the needs of the population. Realization of the principle of self-government enables best division of work between central and local organs. The law on people's councils has strengthened the idea of self-governing by guaranteeing financial basis of economic planning and by defining competences. Decentralization of power and quickening of the activity of state administration, both on central and local levels, as well as establishing its direct ties with the population were the principal aims of these reforms.